The gains and pains of financial integration and trade liberalization : lessons from emerging economies - Bhattacharyya, Rajib (Emerald Publishing Limited, 2019)
The benefits and costs of trade liberalization and financial integration is currently one of the most intensely debated topics in world economics, as the future of the emerging nations of Asia and the fate of more developed countries heavily depends on whether everyone can reap the benefits of this integrated and globalized world. Some believe that increased openness to capital flows has, in general, proved essential for countries seeking to rise from lower- to middle-income status and that removing restrictions on trade and capital flows may usher huge benefits by easing various constraints. Others argue that deregulation of financial markets would have devastating effect on emerging market economies in the long run and that unfettered capital flows may disrupt global financial stability. In The Gains and Pains of Financial Integration and Trade Liberalization: Lessons from Emerging Economies, Rajib Bhattacharyya offers expert insight into these complex debates as he investigates emerging market economies and their recent experiences with these outward-orientation policies. A unique blend of wide-ranging issues and theoretical and empirical depth, this exciting new book includes chapters on dynamic panel models, the measurement of financial integration, the impact of trade openness and financial integration on growth output volatility, and other vital topics. With its focus on real-world issues in emerging markets and its comprehensive coverage of issues such as risk, fiscal policy, and economic effects on income inequality and poverty reduction, Bhattacharyya offers a much-needed contribution to the often all-too-polarised literature. Geared towards policy makers, researchers, academics, and business and management professionals, The Gains and Pains of Financial Integration and Trade Liberalization helps readers develop new theories and models for analysing the future trends in finance and trade-related issues.